Autonomic Modulation During Baseline and Recovery Sleep in Adult Sleepwalkers - Scavone, Geneviève; Baril, Andrée-Ann; Montplaisir, Jacques; Carrier, Julie; Desautels, Alex; Zadra, Antonio (Frontiers in Neurology, 2021)
Sleepwalking has been conceptualized as deregulation between slow-wave sleep and arousal, with its occurrence in predisposed patients increasing following sleep deprivation. Recent evidence showed autonomic changes before arousals and somnambulistic episodes, suggesting that autonomic dysfunctions may contribute to the pathophysiology of sleepwalking. We investigated cardiac autonomic modulation during slow-wave sleep in sleepwalkers and controls during normal and recovery sleep following sleep deprivation. Fourteen adult sleepwalkers (5M; 28.1 ± 5.8 years) and 14 sex- and age-matched normal controls were evaluated by video-polysomnography for one baseline night and during recovery sleep following 25 h of sleep deprivation. Autonomic modulation was investigated with heart rate variability during participants’ slow-wave sleep in their first and second sleep cycles. Five-minute electrocardiographic segments from slow-wave sleep were analyzed to investigate low-frequency (LF) and high-frequency (HF) components of heart rate spectral decomposition. Group (sleepwalkers, controls) X condition (baseline, recovery) ANOVAs were performed to compare LF and HF in absolute and normalized units (nLF and nHF), and LF/HF ratio. When compared to controls, sleepwalkers’ recovery slow-wave sleep showed lower LF/HF ratio and higher nHF during the first sleep cycle. In fact, compared to baseline recordings, sleepwalkers, but not controls, showed a significant decrease in nLF and LF/HF ratio as well as increased nHF during recovery slow-wave sleep during the first cycle. Although non-significant, similar findings with medium effect sizes were observed for absolute values (LF, HF). Patterns of autonomic modulation during sleepwalkers’ recovery slow-wave sleep suggest parasympathetic dominance as compared to baseline sleep values and to controls. This parasympathetic predominance may be a marker of abnormal neural mechanisms underlying, or interfere with, the arousal processes and contribute to the pathophysiology of sleepwalking.